Challenges in the diagnosis of periodic fever, aphthous stomatitis, pharyngitis, and adenitis syndrome in developing countries—A decade of experience from North India - Banday, Aaqib Zaffar; Joshi, Vibhu; Arora, Kanika; Sadanand, Rohit; Basu, Suprit; Pilania, Rakesh Kumar; Jindal, Ankur Kumar; Vignesh, Pandiarajan; Gupta, Anju; Sharma, Saniya; Dhaliwal, Manpreet; Rawat, Amit; et al. (Frontiers in Immunology, 2022)
Background: Reports of PFAPA syndrome from developing countries are sparse. Recognizing PFAPA is often challenging in these regions due to a higher incidence of infectious illnesses and significant resource constraints. Herein, we present our experience from North India regarding the diagnosis and management of PFAPA syndrome. Methods: We reviewed cases of non-monogenic periodic fever syndrome diagnosed at our center from January 2011 to December 2021. A total of 17 children who fulfilled the Marshall criteria for PFAPA syndrome were included. Data regarding basic clinical features, treatment/outcome, and performance of the recently proposed Eurofever/PRINTO and Takeuchi criteria were analyzed. Results: Besides recurrent fever, the triad of oral aphthae, pharyngitis, and adenitis was noted in only 18% patients. Episodes of exudative pharyngitis/tonsillitis were documented in 24%. These figures were lower than the values reported from developed countries. The Takeuchi and Eurofever/PRINTO criteria were fulfilled in 76% and 71% cases, respectively. In addition to antipyretics and supportive care, intermittent steroid therapy was the main treatment modality used. Additional treatment with colchicine (n=3) and thalidomide (n=1) was used successfully in a few patients. Before the diagnosis of PFAPA, all patients had received multiple courses of antimicrobials (without microbiological confirmation). These included multiple courses of antibacterials for fever, pharyngotonsillitis, and/or cervical adenitis in all patients and antivirals for fever and aphthous stomatitis in a patient. Empiric antitubercular therapy had also been administered in 2 patients. Conclusions: A significant proportion of patients with PFAPA seem to remain undiagnosed in the Indian subcontinent. Increased awareness and improvement in basic healthcare facilities are crucial in enhancing the recognition of PFAPA which would eliminate the unprecedented scale of undesirable antimicrobial use in such children.